Kajian Biodegradasi Filem Plastik Campuran Polistiren dengan Poli(3hidroksibutirat-ko-3-hidroksivalerat) dalam Tanah Secara In-vitro - Permatadewi, Asiska; Zaini, Erizal; Rustini, Rustini; Djamaan, Akmal (Jurnal Farmasi Andalas, 2013)
The in vitro biodegradation testing of plastic of the mixture of polystyrene (PS) and poly (3-hydroxybutirate-co-3-hydroxyvalerat) [P(3HB-ko-3HV)] in soil has been carried out. Plastic film was produced by using blending technique and followed by solved casting at various composition. The biodegradation testing was conduted by using soil burial method. Rseult showed that the increasing of component [P(3HB-ko-3HV)] in the mixture of plastic film was also increase the biodegradation rate of plastic film in the soil. At the composition 100:0, 95:5, 90:10 and 85:15 of plastic film in 5 weeks burial was found weigh remaining of plastic were of 99.67; 95.71; 95.03; 94.13% w/w respectively. It is also observed that the amount of bacteria in the soil were of 2.57 x 106 colonies/g.